The Impact of Leadership Factors on Deployment of Environmental Component of Sustainable Development in the Organization - Nastja Tomšič; Blaž Simčič; Mirko Markič (Naše gospodarstvo/Our economy, 2012)
The paper presents the results of the research in which the impact of leadership fac- tors on deployment of environmental components of sustainable development (standard ISO 14001:2004) in large Slovenian organizations was studied. Quantitative research was designed based on 96 fully completed questionnaires. The results indicated that the dominant leadership factors positively affecting the implementati- on of the environmental component of sustainable development in organizations, to which managers should give more attention, are vision, credibility, cooperation, responsibility, and orientation to action.